A disseminação da tradição e a preservação da memória coletiva na era digital - Luvizotto, Caroline Kraus [UNESP] (Liinc em Revista, 2015)
This article addresses the dissemination of traditions and the preservation of collective memory in the broader theoretical context brought by cyberculture studies and new information and communication technologies in the light of late modernity. In this context, the internet and especially web 2.0 tools , considering their specificities and limitations, can approximate social actors with the same binding identity, provide an environment for dissemination and teaching of tradition and preserve the collective memory of a people.

Este artigo situa a disseminação de tradições e a preservação da memória coletiva diante do contexto teórico mais amplo trazido pelos estudos da cibercultura e das novas tecnologias de informação e comunicação, à luz da modernidade tardia. Nesse contexto, a internet e, em especial, as ferramentas da web 2.0, considerando as suas especificidades e limitações, podem aproximar atores sociais com a mesma vinculação identitária; proporcionar um ambiente para a disseminação e ensino de uma tradição e preservar a memória coletiva de um povo.
The dissemination of tradition and the preservation of collective memory in the digital age
Keywords: Tradition; Collective Memory; Cyberculture; Digital Age; Late Modernity; Tradição; Memória coletiva; Cibercultura; Era Digital; Modernidade tardia